A study on factors influence to the political parties membership area: a case study at Kampung Morten / Haniza Abdullah and Nurussakinah Mohamed Hamidi - Abdullah, Haniza; Mohamed Hamidi, Nurussakinah (Faculty of Administrative Science and Policy Studies, 2012)
All the country will face the conflict about the political parties and Malaysia is not excluding from experiencing about the political. The politics of Malaysia takes place in the framework of a federal representative democratic constitutional monarchy. The factors that influence political parties membership are more important for to search. Political party can be defined as a political organization that typically seeks to influence government policy. Political party is also an organized group of people with at least roughly similar political aims and opinions that seek to influence public policy by getting its candidates elected to public office. Parties tend to be deeply and durably entrenched in specific substructures of the specific society in a sustainable and well functioning democracy. It is important to political parties to identify the factor that influence the citizen to join the political party. The contribution of citizen in the political field will create the modern democratic system. For information, the majority of people at Kampung Morten are membership in Barisan Nasional party. Then, majorities the people at Kampung Morten are aging among 40 and above. So, we can search about their political mindset. What we know the issue about political parties is a sensitive issue and we can see also their responsibility as a citizen in Malaysia. The families at Kampung Morten are more than 150 families and majority will support the government because they believe with the political party. They have their own vision about the political party and they know who can give the advantage in their life. The old people and the new generation have own perception about the political issue and the people at kampong Morten still with their membership in Barisan Nasional.